Village Financial Management Towards Village Fund Policy For Community Empowerment - Hastuti (International Journal of Science, Technology & Management, 2021)
The goal of this study is to explain Village Fund Allocation for community empowerment by concentrating on village financial management rules in Village Fund Allocation administration. The Village Fund Allocation Implementation Team's financial management was not in accordance with applicable regulations, thus this research was conducted. This study is expected to assist the Buton Regency Government, specifically the South Lasalimu District, in improving village financial management. The research was conducted through in-depth interviews and direct observation of Village Fund Management implementation. According to the study's results, accountable and transparent management has been in place for the planning and implementation of Village Fund Allocation activities. Meanwhile, in terms of accountability, as indicated by the physical outcomes, it has exhibited responsible and transparent execution; nevertheless, additional direction is still necessary on the administrative side, since it is not completely in conformity with the regulations. The main barrier is the ineffectiveness of developing village government officials and human resource capabilities, which results in a lack of ongoing assistance from local government officials.